Mutation analysis of the STRA6 gene in isolated and non‐isolated anophthalmia/microphthalmia. (4th July 2012) - Chassaing, N; Ragge, N; Kariminejad, A; Buffet, A; Ghaderi‐Sohi, S; Martinovic, J; Calvas, P
<x xml:space="preserve">Abstract</x> PDAC syndrome [Pulmonary hypoplasia/agenesis, Diaphragmatic hernia/eventration, Anophthalmia/microphthalmia (A/M) and Cardiac Defect] is a condition associated with recessive mutations in the STRA6 gene in some of these patients. Recently, cases with isolated anophthalmia have been associated with STRA6 mutations. To determine the minimal findings associated with STRA6 mutations, we performed mutation analysis of the STRA6 gene in 28 cases with anophthalmia. In 7 of the cases the anophthalmia was isolated, in 14 cases it was associated with one of the major features included in PDAC and 7 had other abnormalities. Mutations were identified in two individuals: one with bilateral anophthalmia and some features included in PDAC, who was a compound heterozygote for a missense mutation and a large intragenic deletion, and the second case with all the major features of PDAC and who had a homozygous splicing mutation. This study suggests that STRA6 mutations are more likely to be identified in individuals with A/M and other abnormalities included in the PDAC spectrum, rather than in isolated A/M cases.